Least limiting water range in soil under crop rotations and chiseling - Calonego, Juliano Carlos [UNESP]; Rosolem, Ciro Antonio [UNESP] (Sociedade Brasileira de Ciência do Solo, 2011)
Soil water availability to plants is affected by soil compaction and other variables. The Least Limiting Water Range (LLWR) comprises soil physical variables affecting root growth and soil water availability, and can be managed by either mechanical or biological methods. There is evidence that effects of crop rotations could last longer than chiseling, so the objective of this study was to assess the effect of soil chiseling or growing cover crops under no-till (NT) on the LLWR. Crop rotations involving triticale (X Triticosecale) and sunflower (Helianthus annuus) in the fall-winter associated with millet (Pennisetum glaucum), sorghum (Sorghum bicolor) and sunn hemp (Crotalariajuncea) as cover crops preceding soybean (Glycine max) were repeated for three consecutive years. In the treatment with chiseling (performed. only in the first year), the area was left fallow between the fall-winter and summer crops. The experiment was carried out in Botucatu, São Paulo State, Brazil, from 2003 to 2006 on a Typic Rhodudalf. The LLWR was determined in soil samples taken from the layers 0-20 cm and 20-40 cm, after chemical desiccation of the cover crops in December of the first and third year of the experiment. Chiseling decreases soil bulk density in the 0-20 cm soil layer, increasing the LLWR magnitude by lowering the soil water content at which penetration resistance reaches 2.0 MPa; this effect is present up to the third year after chiseling and can reach to a depth of 0.40 in. Crop rotations involving sunflower + sunn hemp, triticale + millet and triticale + sunn hemp for three years prevented soil bulk density from exceeding the critical soil bulk density in the 0-0.20 in layer. This effect was observed to a depth of 0.40 m after three years of chiseling under crop rotations involving forage sorghum. Hence, chiseling and some crop rotations under no tillage are effective in increasing soil quality assessed by the LLWR.

A disponibilidade de água às plantas é alterada pela compactação do solo e outras variáveis. O Intervalo Hídrico Ótimo (IHO) integra variáveis físicas do solo que alteram o crescimento radicular e a disponibilidade de água e pode ser manejado por métodos mecânicos ou biológicos. Há evidências de que os efeitos da rotação de culturas são mais duradouros que os da escarificação. O objetivo deste trabalho foi avaliar o efeito da escarificação e, ou, rotação de culturas em sistema de semeadura direta (SSD) no IHO. Rotações envolvendo triticale (X Triticosecale) e girassol (Helianthus annuus) no outono-inverno e milheto (Pennisetum glaucum), sorgo (Sorghum bicolor) e crotalária (Crotalaria juncea) com plantas de cobertura precedendo a soja (Glycine max) foram repetidas por três anos. No tratamento com escarificação, a área foi deixada em pousio entre as culturas de outono-inverno e verão. O experimento foi conduzido em Botucatu, São Paulo, Brasil, de 2003 a 2006 em um Nitossolo Vermelho. O IHO foi determinado em amostras de solo das profundidades de 0-20 e 20-40 cm, logo após a dessecação química das plantas de cobertura, em dezembro do primeiro e do terceiro ano do experimento. A escarificação diminui a densidade do solo na camada de 0-20 cm, aumentando o IHO por meio da redução da umidade do solo em que a resistência à penetração atinge 2,0 MPa; esse efeito mantém-se até o terceiro ano após a escarificação, podendo chegar a até 40 cm de profundidade. As rotações de culturas envolvendo girassol + crotalária, triticale + milheto e triticale + crotalária por três anos ajudaram a prevenir o aumento na densidade do solo acima do valor crítico na camada de 0-20 cm. Esse efeito é observado na camada de 20- 40 cm após três anos da escarificação e com rotações de culturas envolvendo sorgo. Assim, a escarificação e algumas rotações de culturas em sistema de semeadura direta são eficientes em melhorar a qualidade do solo avaliada pelo IHO.
Intervalo hídrico ótimo em solo sob rotação de culturas e escarificação
Keywords: cover crops; crop rotation; soil compaction; no till; soil water